Molecular cloning and expression of a murine homolog of the human poliovirus receptor gene. - Morrison, M E (1992)
The poliovirus receptor (Pvr) is a member of the immunoglobulin superfamily of proteins, but its function in the cell is not known. Southern blot hybridization analysis indicated that the murine genome contains a sequence homolog of pvr. As a first step toward using the murine pvr homolog (mph) to study the function of Pvr, murine genomic and cDNA clones encoding mph were isolated. mph encodes a polypeptide with extensive sequence similarity to the extracellular domains of the human PVR. mph mRNAs of 2.0 and 3.0 kb are transcribed in the adult mouse brain, the spinal cord, the spleen, the kidney, the heart, and the liver. The Mph protein does not function as a receptor for poliovirus. However, substitution of domain 1 of the Mph protein with the corresponding sequence from pvr produced a chimeric receptor that could bind poliovirus and lead to productive infection. By constructing pvr-mph chimeras, it will be possible to identify the contact points of poliovirus within domain 1 of Pvr. Identification of the ligand and the cellular function of the Mph protein may help us understand the role of Pvr in the cell.